Projeto de letramento na escola: possibilidade para ampliar a participação social dos alunos por meio de práticas de escrita - Dassayelle Monteiro Dias (2016)
This study aims to build a literacy project that allows to develop social writing practices from real situations and to reflect on the process of this construction. Literacy projects, according to Kleiman (2000), are conceived as a set of activities whose implementation involves the use of writing for the wide circulation of texts inside and outside the school. These projects focus on broader social issues in which writing is embedded and learned or appropriated from the interests and needs of students. This study intends to contribute to the development of new teaching strategies in the school that promote the students' social participation through literacy practices. For this, conceiving language as an interactive practice, we take as theoretical presuppositions studies by authors such as Bakhtin (2003); Kleiman (1995, 2000, 2006, 2007, 2008, 2010); Kleiman, Ceniceros and Tinoco (2013); Marcuschi (2008, 2011); Oliveira (2010); Oliveira and Santos (2012); Oliveira, Santos and Tinoco (2014); Rojo (2010); Stret (2010); and Tinoco (2009). The present work was developed with a 6th grade class from Elementary School II of a school in the city of São Joaquim de Bicas / MG. Based on a problem experienced by the community - the growing use of drugs among residents of the region - students decided to write a memoir of ex-users of legal and illegal drugs directed to the school community, in order to alert the target audience on the dangers of drugs and encourage people not to consume these substances. For the production of the memoirs, students sought information through the recording of testimony of ex-drug user and oral interviews with the deponent, family member or friend of the deponent. In this way, the literacy project first establishes the social practice in which students will be involved; then it lists the genres of discourse needed to be explored to allow students to act discursively and in which literacy events they should be involved in order to achieve the objectives of the project, which has been implemented through tasks, so that such an organization enabled the development of skills necessary for the production of memories. The impact of social action, through the genre of memories, was perceived by students and this may encourage them to continue acting in society through the use of writing, once they have experienced a language education for citizenship.